2017
DOI: 10.1177/0961203317709347
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies against complement components in systemic lupus erythematosus – role in the pathogenesis and clinical manifestations

Abstract: Many complement structures and a number of additional factors, i.e. autoantibodies, receptors, hormones and cytokines, are implicated in the complex pathogenesis of systemic lupus erythematosus. Genetic defects in the complement as well as functional deficiency due to antibodies against its components lead to different pathological conditions, usually clinically presented. Among them hypocomplementemic urticarial vasculitis, different types of glomerulonephritis as dense deposit disease, IgA nephropathy, atypi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Compared with SLE patients without hematologic involvement, the levels of complement C3 and C4 in SLE patients with hematologic involvement were lower. Previous studies 12 , 13 have shown that IgG, C3 and C4 can be used as indicators to monitor the active stage of SLE disease, and hematologic involvement in the clinical diagnostic guidelines of SLE disease was also classified as the performance of SLE disease activity. The results of this study were proved to be reliable.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with SLE patients without hematologic involvement, the levels of complement C3 and C4 in SLE patients with hematologic involvement were lower. Previous studies 12 , 13 have shown that IgG, C3 and C4 can be used as indicators to monitor the active stage of SLE disease, and hematologic involvement in the clinical diagnostic guidelines of SLE disease was also classified as the performance of SLE disease activity. The results of this study were proved to be reliable.…”
Section: Discussionmentioning
confidence: 99%
“…However, the association of acquired angioedema with SLE is welldescribed, and some cases have been attributed to decreased C1-INH levels caused by increased catabolism or autoantibodies. 47,48 Autoantibodies against complement components in patients with SLE can also cause hypocomplementemic urticarial vasculitis, 49,50 a distinctive type of vasculitis with multi-organ involvement, which could explain "all sorts of skin lesions" and "chronic nephritis" in the case of Mrs M. (Current opinion supports Osler's statement that "there is really no warrant for separating too sharply angio-neurotic oedema and urticaria." 36 ) The association of angioedema with HSP is less prominent, although both conditions were present in one of Osler's cases 41 :…”
Section: Differential Diagnosis In the "Case Of Mrs M"mentioning
confidence: 93%
“…LN pathogenesis mainly includes immune complex lesions ( Anders and Fogo, 2014 ) and epigenetic abnormalities ( Dieker, et al 2007 ). In addition, abnormalities in the complement system ( Hristova and Stoyanova, 2017 ), sexual hormone disorders ( Feng, et al 2010 ), and environmental effects are also related to the occurrence and development of LN.…”
Section: Nephropathymentioning
confidence: 99%